Management of the Intensity of the Flow of Buyers of the Retail Network - Ivan Burtnyak; Ivan Blahun; Oleksandr Kusnir (Vasyl Stefanyk Precarpathian National University, 2024)
An approach to the management of customer flows is considered, which takes into account the uniformity of the daily intensity as an efficiency criterion. An intensity model is proposed to assess the degree of uniformity. A new formulation of the task of managing the flow of buyers has been introduced, the main feature of which is the criterion of management efficiency, based not on the economic effect, but on the uniformity of the flow. At the same time, the time of making a purchase is, as a rule, a random value. Then the ratio of the instantaneous intensity of the flow and its power per day is the probability of visiting the store at a certain point in time. The relative intensity thus specified can be examined using the density function of the purchase time distribution. To assess uniformity, it is suggested to switch to the daily flow intensity model. The built map of the cluster structure of flows allows you to visually analyze the effectiveness of managing the intensity of customer flows, in particular, during peak pricing activities. The economic effect is justified by the economic benefit, which is achieved not only due to the equalization of the intensity of the purchase flow during the day, but also due to the increase in the volume of sales, which compensates for the reduction of the mark-up in periods of low purchase activity. Therefore, along with the relative intensity, changes in the power of the flow and its qualitative composition according to the average purchase volume were also studied. The purpose of the study is to assess the effectiveness of peak pricing measures in terms of smoothing daily fluctuations in the intensity of the flow of buyers in retail chains. To achieve the goal, a new formulation of the task of managing the flow of buyers was introduced, the main feature of which is the criterion of management efficiency, based not on the economic effect, but on the uniformity of the flow. To assess such uniformity, it is suggested to switch to the daily flow intensity model. It is important to take into account the relationship between the characteristics of the structural components of the flow on one of the components leading to a change in the intensity of the other. In general, the proposed formulation of the task of flow management and the model of its intensity are also applicable in the activities of companies of other types of economic activity that face the problem of peak demand, for example, in the electric power sector. This opens up opportunities to identify new patterns in consumer behavior.